Laparoscopic Reduction of Intussusception in a 13-Year-Old Girl with Multiple Intestinal Polyps - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Intussusception has been one of the common causes of intestinal obstruction in infancy and early childhood period with a challenge in diagnosis in older children. It is the telescoping of a segment of bowel into another, commonly a proximal segment into a distal one. Intussusception in infancy and early childhood is usually primary or idiopathic as there is no associated pathological lead point involved. However, in older children and adult, there is most often time an identifiable lead point that predisposes to the intussusception.